2018
DOI: 10.3390/ijms19092577
|View full text |Cite
|
Sign up to set email alerts
|

Are Colon and Rectal Cancer Two Different Tumor Entities? A Proposal to Abandon the Term Colorectal Cancer

Abstract: Colon cancer (CC) and rectal cancer (RC) are synonymously called colorectal cancer (CRC). Based on our experience in basic and clinical research as well as routine work in the field, the term CRC should be abandoned. We analyzed the available data from the literature and results from our multicenter Research Group Oncology of Gastrointestinal Tumors termed FOGT to confirm or reject this hypothesis. Anatomically, the risk of developing RC is four times higher than CC, while physical activity helps to prevent CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
153
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 135 publications
(218 reference statements)
5
153
0
4
Order By: Relevance
“…With this regard, compound 20 may be an attractive agent for systemic treatment of metastatic disease. Individual screening and molecular subtyping may help in the future to identify possible candidates for such a targeted therapy [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this regard, compound 20 may be an attractive agent for systemic treatment of metastatic disease. Individual screening and molecular subtyping may help in the future to identify possible candidates for such a targeted therapy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…At present, a five-year survival rate of 12% for stage IV disease has been reported for the US [18]. In order to further improve outcome, treatment of stage IV disease has to be optimized probably by further individualization according to the respective disturbances found [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the location of the tumor, the presence of G/A and A/A genotypes for the rs187116 polymorphism (OR = 3.63; 95% CI = 1.55-8.49, P = 0.003, OR = 4.16; 95% CI = 1.60-10.8, P = 0.003) respectively and the presence of G/G genotype for rs7116432 polymorphism (OR = 5.94; 95% CI = 2.40-14.7, P = 0.001) were associated with an increased risk for tumor development in the colon. In support of these results, studies achieved in Western countries found that two-thirds of CRC is in the colon, and only one third in the rectum (Paschke et al 2018). Such a difference could be explained with the considerable length of the colon and consequently, a more extensive mucosa where a tumor could eventually start.…”
Section: Discussionmentioning
confidence: 53%
“…The colorectum can anatomically be divided in the proximal colon, distal colon, and rectum. Depending on the anatomical subsite, colorectal tumors may develop through distinct molecular pathways and show varying patterns of (epi) genetic changes [21,22]. Furthermore, differences have been shown in subsite-specific incidence trends and survival [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the anatomical subsite, colorectal tumors may develop through distinct molecular pathways and show varying patterns of (epi) genetic changes [21,22]. Furthermore, differences have been shown in subsite-specific incidence trends and survival [21,22]. Because of their potentially distinct etiologies, cancers of the proximal colon, distal colon, and rectum should initially be considered as separate endpoints in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%